Propriedades ópticas e elétricas de materiais híbridos de sílica/orgânico à base de GPTS:TEOS preparados pelo método sol-gel - Quadros, Matheus Henrique [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Fabrication of optoelectronic devices requires the employment of at least one transparent electrode. Usually, commercially transparent electrodes have been made by deposition of indium tin oxide (ITO) films by RF-Sputtering technique. These commercial electrodes have sheet resistance of about 100 Ω/sq and optical transmittance of 77% at the wavelength of 550 nm. The poly(3,4-ethylenedioxythiophene):polystyrene-sulfonate (PEDOT:PSS) is an alternative material to fabricate transparent electrodes due to its high conductivity (about 600 S/cm) and solubility in water. Soluble conductive materials exhibits advantages for processing of electrode layers, however there is a disadvantage during devices fabrication once materials with the same solvent of the electrode material cannot be coated one over the other. Alternatively, organic/Silica hybrid materials prepared by sol-gel process allow producing bulks and films with high chemical durability. In order to obtain transparent electrodes with high chemical durability, we introduced a blended material comprising the high UV-VIS transparency of organic/Silica sol-gel material and a high conductivity polymer PEDOT:PSS. The organic/Silica sol was obtained using two different molar concentrations (1:1 and 4:1), of tetraethylorthosilicate (TEOS) and 3-glycidoxypropyltrimethoxysilane (GPTS). Amounts of PEDOT:PSS solutions were added to the sol material, resulting in different weight fractions of sol and polymer. G:T/P:P were deposit onto glass substrates by spray-coating. In order to perform electrical characterization of the blended material, gold electrodes were thermally evaporated onto the films. The electrical characterization was performed using a Keithley 2410 source/meter unity and the optical characterization, using a Cary50 UV-Vis spectrophotometer. The absorption coefficient and electric conductivity of the different compositions blends, as function of the PEDOT:PSS concentration, were...

A fabricação de dispositivos optoeletrônicos requer o emprego de no mínimo um eletrodo transparente. Normalmente, eletrodos transparentes comerciais são fabricados com óxidos transparentes, sendo o mais comum o óxido de índio-estanho (ITO), e depositados por técnicas como RF-Sputtering, apresentando baixa resistência de folha ( menor que 100 Ω/sq (sq = quadrado) e transmitância óptica acima de 75% em 550 nm. O poli(3,4-etileno dioxitiofeno):poliestireno sulfonado (PEDOT:PSS) é um material alternativo solúvel em água para fabricação de eletrodos transparentes que pode alcançar alta condutividade (~900 S/cm) quando dopado com etilenoglicol ou dimetil sulfóxido. O PEDOT:PSS apresenta vantagem no processamento de camadas de eletrodos, porém a desvantagem aparece na fabricação de dispositivos que contenham camadas do mesmo solvente, uma vez que estas camadas dissolveriam os eletrodos de PEDOT:PSS. Por outro lado, materiais híbridos de sílica/orgânico preparados por processo sol-gel possibilitam a produção de filmes insolúveis em diversos solventes, como a água, apresentando alta estabilidade química. Com o objetivo de obter eletrodos insolúveis em água e transparentes no UV-VIS, uma matriz compreendendo os materiais híbridos de sílica/orgânico foi produzida a partir dos alcóxidos de silício 3-glicidoxipropiltrimetoxisilano (GPTS) e tetraetilortosilicato (TEOS), onde posteriormente foi acrescentado o polímero condutor PEDOT:PSS. O sol de sílica/orgânico foi obtido com duas concentrações diferentes, GPTS:TEOS(1:1) e GPTS:TEOS(1:4). Diferentes quantidades da solução de PEDOT:PSS foram adicionadas ao sol de GPTS:TEOS, resultando em blendas com diferentes concentrações em massa do GPTS:TEOS e do polímero. As blendas de GPTS:TEOS/PEDOT:PSS foram depositadas em substratos de vidro pela técnica de Spray-coating, formando filmes (G:T:1/P:P e G:T:4/P:P) com espessuras da ordem de um micrometro. As propriedades...
Keywords: Fisica otica; Silica; Processo sol-gel; Polimeros condutores; Polimeros - Propriedades eletricas; Polímeros - Propriedades óticas